Resin composition, prepreg, resin film, laminate, printed wiring board and semiconductor package
The thermosetting resin composition with a tailored particle size distribution of inorganic fillers addresses the challenge of reducing dielectric loss tangent and improving circuit embeddingability, achieving enhanced performance in dielectric properties and embeddingability.
Patent Information
- Application Number
- JP2023175301
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-10
- Publication Date
- 2025-04-22
AI Technical Summary
Existing resin compositions struggle to simultaneously reduce the dielectric loss tangent (Df) and improve circuit embeddingability, as increasing the particle size of inorganic fillers reduces Df but deteriorates embeddingability.
A thermosetting resin composition with a specific particle size distribution of inorganic fillers, where the average particle diameter of the larger peak is greater than that of the smaller peak, and the content ratio of the larger peak filler is between 1/99 to 40/60, is used to achieve both low Df and improved embeddingability.
The resin composition effectively reduces the dielectric loss tangent (Df) and enhances circuit embeddingability, while also improving peel strength and heat resistance.
Smart Images

Figure 2025065832000006 
Figure 2025065832000001 
Figure 2025065832000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a resin composition, a prepreg, a resin film, a laminate, a printed wiring board, and a semiconductor package. [Background technology]
[0002] In various electronic devices such as mobile communication devices such as mobile phones, their base station equipment, network infrastructure devices such as servers and routers, and large computers, the speed and capacity of signals used are increasing year by year. Accordingly, the printed wiring boards mounted on these electronic devices must be compatible with higher frequencies, and there is a demand for board materials with small dielectric loss tangent (Df) in high frequency bands that can reduce transmission loss. In recent years, in addition to the above-mentioned electronic devices, new systems that handle high-frequency wireless signals have been put into practical use or are planned to be put into practical use in the ITS field, such as automobiles and traffic systems, and in the field of indoor short-range communication, as applications that handle such high-frequency signals, and low transmission loss board materials are also required for the printed wiring boards mounted on these devices.
[0003] Furthermore, the substrate material may be required to have the ability to embed a resin component in a circuit pattern (circuit embedding ability), and it is known that lowering the minimum melt viscosity of the substrate material is an effective way to improve wiring embedding ability (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2018-012777 A Summary of the Invention [Problem to be solved by the invention]
[0005] The inventors' research has revealed that increasing the particle size of the inorganic filler in the substrate material can reduce the dielectric loss tangent (Df), which contributes to low transmission loss. On the other hand, it has been found that increasing the particle size of the inorganic filler deteriorates the circuit embeddability, and it has been found that it is not easy to achieve both a reduction in the dielectric loss tangent (Df) and an improvement in the circuit embeddability at the same time.
[0006] In view of the current situation, the present disclosure has an object to provide a resin composition capable of reducing the dielectric tangent (Df) and improving the circuit embedding property, and to provide a prepreg, a resin film, a laminate, a printed wiring board, and a semiconductor package obtained using the resin composition. [Means for solving the problem]
[0007] As a result of extensive research, the present inventors have found that the thermosetting resin composition of the present disclosure can achieve the above object.
[0008] The present disclosure includes the following embodiments [1] to
[12] . [1] A thermosetting resin composition comprising (A) a thermosetting resin and (B) an inorganic filler, The (B) inorganic filler has a peak maximum (B1) and a peak maximum (B2) in a particle size distribution, the average particle size (b1) of the inorganic filler corresponding to the entire peak having the maximum (B1) is greater than the average particle size (b2) of the inorganic filler corresponding to the entire peak having the maximum (B2), and the ratio of the content of the inorganic filler corresponding to the entire peak having the maximum (B1) to the content of the inorganic filler corresponding to the entire peak having the maximum (B2) is 1 / 99 to 40 / 60. [2] The resin composition according to the above [1], wherein the average particle size (b1) of the inorganic filler corresponding to the entire peak having the maximum (B1) is 1.5 μm or less. [3] The resin composition according to the above [1] or [2], wherein the average particle size (b2) of the inorganic filler corresponding to the entire peak having the maximum (B2) is greater than 1.5 μm. [4] The resin composition according to any one of the above [1] to [3], wherein the (A) thermosetting resin comprises at least one selected from the group consisting of an epoxy resin, a maleimide compound, a modified polyphenylene ether resin, a phenolic resin, a polyimide resin, a cyanate resin, an isocyanate resin, a benzoxazine resin, an oxetane resin, an amino resin, an unsaturated polyester resin, an allyl resin, a dicyclopentadiene resin, a silicone resin, a triazine resin, and a melamine resin. [5] The resin composition according to any one of the above [1] to [4], further comprising (C) an elastomer. [6] The resin composition according to any one of the above [1] to [5], further comprising (D) a compatibilizer. [7] The resin composition according to any one of the above [1] to [6], further comprising (E) a curing accelerator. [8] A prepreg comprising the resin composition according to any one of the above [1] to [7] or a semi-cured product of the resin composition. [9] A resin film comprising the resin composition according to any one of the above [1] to [7] or a semi-cured product of the resin composition.
[10] A laminate comprising a cured product of the resin composition according to any one of the above [1] to [7] and a metal foil.
[11] A printed wiring board having a cured product of the resin composition according to any one of [1] to [7] above.
[12] A semiconductor package comprising the printed wiring board according to
[11] above and a semiconductor element. Effect of the Invention
[0009] The present disclosure makes it possible to provide a resin composition capable of reducing the dielectric tangent (Df) and improving the circuit embedding property, as well as to provide a prepreg, a resin film, a laminate, a printed wiring board, and a semiconductor package obtained using the resin composition. [Brief description of the drawings]
[0010] [Figure 1] FIG. 2 is an image diagram of the particle size distribution of the inorganic filler (B) contained in the resin composition of the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] In the numerical ranges described in the present disclosure, the upper or lower limit of the numerical range may be replaced with the values shown in the examples. In addition, the lower and upper limits of a numerical range may be arbitrarily combined with the lower or upper limit of another numerical range. In the expression of a numerical range "AA to BB", the numerical values AA and BB at both ends are included in the numerical range as the lower and upper limits, respectively. In this disclosure, for example, the term "10 or more" means 10 or a number greater than 10, and the same applies when the numbers are different. Also, for example, the term "10 or less" means 10 or a number less than 10, and the same applies when the numbers are different. Also, the term "greater than 10" means a number greater than 10, and the same applies when the numbers are different. In addition, each component and material exemplified in this disclosure may be used alone or in combination of two or more types, unless otherwise specified. In this disclosure, the content of each component in the composition means the total amount of the multiple substances present in the composition when multiple substances corresponding to each component are present in the composition, unless otherwise specified.
[0012] In the present disclosure, the term "resin component" refers to all components among the solid contents constituting the resin composition, excluding inorganic compounds such as inorganic fillers described below. In the present disclosure, the term "solid content" refers to components other than the organic solvent described below, and components that are liquid at 25°C are also considered to be solid content. The expression "containing XX" described in the present disclosure means that it may be in either an embodiment that XX is contained in a reacted state when XX is capable of reacting, or that XX is simply contained. Any combination of the descriptions in this disclosure is also included in this disclosure and this embodiment.
[0013] [Resin composition] The resin composition of this embodiment is as follows. A resin composition comprising (A) a thermosetting resin (hereinafter, sometimes referred to as component (A)) and (B) an inorganic filler (hereinafter, sometimes referred to as component (B)), The (B) inorganic filler has a peak maximum (B1) and a peak maximum (B2) in a particle size distribution, the average particle size (b1) of the inorganic filler corresponding to the entire peak having the maximum (B1) is greater than the average particle size (b2) of the inorganic filler corresponding to the entire peak having the maximum (B2), and the ratio of the content of the inorganic filler corresponding to the entire peak having the maximum (B1) to the content of the inorganic filler corresponding to the entire peak having the maximum (B2) is 1 / 99 to 40 / 60. The components contained in the resin composition of the present embodiment will be described in detail below.
[0014] ((A) Thermosetting resin) The component (A) preferably contains at least one selected from the group consisting of epoxy resins, maleimide compounds, modified polyphenylene ether resins, phenolic resins, polyimide resins, cyanate resins, isocyanate resins, benzoxazine resins, oxetane resins, amino resins, unsaturated polyester resins, allyl resins, dicyclopentadiene resins, silicone resins, triazine resins, and melamine resins, more preferably contains at least one selected from the group consisting of epoxy resins, maleimide compounds, modified polyphenylene ether resins, phenolic resins, polyimide resins, cyanate resins, and isocyanate resins, and further preferably contains at least one selected from the group consisting of epoxy resins and maleimide compounds, and from the viewpoint of low thermal expansion, etc., it is particularly preferable to contain a maleimide compound. The modified polyphenylene ether resin is preferably a polyphenylene ether resin having an ethylenically unsaturated bond-containing group at the terminal, and more preferably a polyphenylene ether resin having an ethylenically unsaturated bond-containing group at both terminals. Examples of the ethylenically unsaturated bond-containing group include unsaturated aliphatic hydrocarbon groups such as a vinyl group, an allyl group, a 1-methylallyl group, an isopropenyl group, a 2-butenyl group, a 3-butenyl group, and a styryl group; and groups containing a hetero atom and an ethylenically unsaturated bond, such as a maleimide group and a (meth)acryloyl group. As the component (A), one type may be used alone, or two or more types may be used in combination.
[0015] The epoxy resin is preferably an epoxy resin having two or more epoxy groups in one molecule. Here, the epoxy resin is classified into glycidyl ether type epoxy resin, glycidyl amine type epoxy resin, glycidyl ester type epoxy resin, etc. Among these, glycidyl ether type epoxy resin is preferable. Epoxy resins are also classified into various epoxy resins depending on the difference in the main skeleton, and each of the above types of epoxy resins is further classified into bisphenol type epoxy resins such as bisphenol A type epoxy resins, bisphenol F type epoxy resins, and bisphenol S type epoxy resins; alicyclic epoxy resins such as dicyclopentadiene type epoxy resins; aliphatic linear epoxy resins; novolac type epoxy resins such as phenol novolac type epoxy resins, cresol novolac type epoxy resins, bisphenol A novolac type epoxy resins, bisphenol F novolac type epoxy resins, phenol aralkyl novolac type epoxy resins, and biphenyl aralkyl novolac type epoxy resins; stilbene type epoxy resins; naphthalene skeleton-containing epoxy resins such as naphthol novolac type epoxy resins and naphthol aralkyl type epoxy resins; biphenyl type epoxy resins; xylylene type epoxy resins; and dihydroanthracene type epoxy resins.
[0016] The maleimide compound preferably includes at least one selected from the group consisting of maleimide compounds having one or more (preferably two or more) N-substituted maleimide groups and derivatives thereof. The maleimide compound having one or more N-substituted maleimide groups is not particularly limited, and examples thereof include aromatic maleimide compounds having one N-substituted maleimide group bonded to an aromatic ring, such as N-phenylmaleimide, N-(2-methylphenyl)maleimide, N-(4-methylphenyl)maleimide, N-(2,6-dimethylphenyl)maleimide, N-(2,6-diethylphenyl)maleimide, N-(2-methoxyphenyl)maleimide, and N-benzylmaleimide; 4,4'-diphenylmethane bismaleimide, bis(4-maleimidophenyl)ether, bis(4-maleimidophenyl)sulfone, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 4-methyl-1 aromatic bismaleimide compounds having preferably two N-substituted maleimide groups bonded to an aromatic ring, such as 3-phenylene bismaleimide, m-phenylene bismaleimide, 2,2-bis[4-(4-maleimidophenoxy)phenyl]propane, and indane ring-containing aromatic bismaleimide; aromatic polymaleimide compounds having preferably three or more N-substituted maleimide groups bonded to an aromatic ring, such as polyphenylmethane maleimide and biphenyl aralkyl maleimide; and aliphatic maleimide compounds such as N-dodecylmaleimide, N-isopropylmaleimide and N-cyclohexylmaleimide, 1,6-bismaleimide-(2,2,4-trimethyl)hexane, and pyrrolidine binder type long-chain alkyl bismaleimide. Among these, from the viewpoints of compatibility with other resins, adhesion to conductors, heat resistance, low thermal expansion, mechanical properties, and dielectric tangent (Df), aromatic bismaleimide compounds having two N-substituted maleimide groups bonded to an aromatic ring are more preferred, and 4,4'-diphenylmethane bismaleimide and indane ring-containing aromatic bismaleimide are even more preferred. In the maleimide compound, it is preferable that the nitrogen atom of each of "one N-substituted maleimide group preferably bonded to an aromatic ring", "two N-substituted maleimide groups preferably bonded to an aromatic ring", and "three or more N-substituted maleimide groups preferably bonded to an aromatic ring" is bonded to an aromatic ring. Thus, it is preferable that the nitrogen atoms of the N-substituted maleimide groups in the maleimide compound are bonded to each other via a linking group containing an aromatic ring.
[0017] Examples of the derivatives of the maleimide compound include addition reaction products of a maleimide compound having one or more (preferably two or more) N-substituted maleimide groups and an amine compound such as a monoamine compound or a diamine compound. Examples of the monoamine compound include monoamine compounds having an acidic substituent, such as o-aminophenol, m-aminophenol, p-aminophenol, o-aminobenzoic acid, m-aminobenzoic acid, p-aminobenzoic acid, o-aminobenzenesulfonic acid, m-aminobenzenesulfonic acid, p-aminobenzenesulfonic acid, 3,5-dihydroxyaniline, and 3,5-dicarboxyaniline. Examples of the diamine compound include 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylethane, 4,4'-diaminodiphenylpropane, 2,2'-bis(4,4'-diaminodiphenyl)propane, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-diethyl-4,4'-diaminodiphenylmethane, 3,3'-dimethyl-4,4'-diaminodiphenylethane, 3,3'-diethyl-4,4'-diaminodiphenylethane, 4,4'-diaminodiphenyl ether, Examples of the suitable diaminodiphenyl thioether include 4,4'-dihydroxy-4,4'-diaminodiphenylmethane, 2,2',6,6'-tetramethyl-4,4'-diaminodiphenylmethane, 3,3'-dichloro-4,4'-diaminodiphenylmethane, 3,3'-dibromo-4,4'-diaminodiphenylmethane, 2,2',6,6'-tetrachloro-4,4'-diaminodiphenylmethane, 2,2',6,6'-tetrabromo-4,4'-diaminodiphenylmethane, and siloxane diamine.
[0018] (Content of component (A)) The content of component (A) in the resin composition of the present embodiment is not particularly limited, but from the viewpoints of heat resistance and moldability, it is preferably 1 to 95 mass %, more preferably 3 to 80 mass %, even more preferably 5 to 60 mass %, particularly preferably 5 to 40 mass %, and most preferably 5 to 25 mass %, relative to the total amount of solids in the resin composition.
[0019] ((B) Inorganic filler) As shown in FIG. 1, the (B) inorganic filler has a peak maximum (B1) and a peak maximum (B2) in the particle size distribution, and the average particle size (b2) of the inorganic filler corresponding to the entire peak having the maximum (B2) is larger than the average particle size (b1) of the inorganic filler corresponding to the entire peak having the maximum (B1), and the content of the inorganic filler corresponding to the entire peak having the maximum (B2) is 1 / 99 to 40 / 60 relative to the content of the inorganic filler corresponding to the entire peak having the maximum (B2). Here, in the present disclosure, the particle size refers to the particle size of the primary particles. Also, in the present disclosure, the average particle size refers to the volume average particle size (D50), which is the particle size at the point corresponding to 50% volume when a cumulative frequency distribution curve is calculated based on the particle size with the total volume of the particles being 100%. Note that D50 is a value measured with a particle size distribution measuring device using a laser diffraction scattering method, and in detail, a value measured by the method described in the Examples. The (B) component can reduce the dielectric loss tangent (Df) of the cured resin composition and improve the circuit embedding property. The reason why this effect is obtained is presumed as follows. The inorganic filler having a larger particle size has the effect of reducing the dielectric loss tangent (Df), and the inorganic filler having a smaller particle size enters the gaps between the inorganic fillers having a larger particle size, thereby increasing the proportion of the resin component that can contribute to flow and decreasing the minimum melt viscosity, thereby improving the circuit embedding property. However, even if the above presumption is not accurate, it does not affect the scope of the present disclosure or the present embodiment.
[0020] In addition to the above effects, it was found that component (B) also tends to improve the adhesive strength (peel strength) with the conductor. The reason for this effect is presumed to be as follows. It is believed that the inorganic filler having a smaller particle size penetrates into the gaps between the inorganic fillers having a larger particle size, thereby reducing the inorganic filler present on the surface of the resin composition, thereby improving the peel strength. However, even if the above speculation is not accurate, it does not affect the scope of the present disclosure or the present embodiment.
[0021] The average particle size (b1) of the inorganic filler corresponding to the entire peak having the maximum (B1) is preferably 1.5 μm or less, more preferably 0.1 to 1.5 μm, even more preferably 0.3 to 1.5 μm, particularly preferably 0.5 to 1.3 μm, and most preferably 0.7 to 1.3 μm. The average particle size (b2) of the inorganic filler corresponding to the entire peak having the maximum (B2) is preferably more than 1.5 μm, more preferably from more than 1.5 μm to 3.5 μm, even more preferably from 1.7 to 3.5 μm, particularly preferably from 1.8 to 3.0 μm, and most preferably from 1.8 to 2.6 μm. When the inorganic filler has the average particle size (b1) or the average particle size (b2), the inorganic filler having a smaller particle size can easily enter the gaps between the inorganic fillers having a larger particle size, and the effects of the present invention tend to be more easily manifested.
[0022] As described above, the ratio of the content of the inorganic filler corresponding to the entire peak having the local maximum (B1) to the content of the inorganic filler corresponding to the entire peak having the local maximum (B2) is 1 / 99 to 40 / 60. This embodiment allows the inorganic filler having a smaller particle size to enter the gaps between the inorganic fillers having a larger particle size, making it easier to reduce the amount of the inorganic filler having a smaller particle size spilling out of the gaps. From the same viewpoint, the content of the inorganic filler corresponding to the entire peak having the local maximum (B1) relative to the content of the inorganic filler corresponding to the entire peak having the local maximum (B2) is preferably 5 / 95 to 40 / 60, more preferably 10 / 90 to 40 / 60, even more preferably 10 / 90 to 35 / 65, particularly preferably 15 / 85 to 35 / 65, and most preferably 20 / 80 to 30 / 70. The resin composition of this embodiment may be a resin composition obtained by blending (A) a thermosetting resin and (B) an inorganic filler such that the blending amount of the inorganic filler having the average particle size (b1) relative to the blending amount of the inorganic filler having the average particle size (b2) is preferably 5 / 95 to 40 / 60, more preferably 10 / 90 to 40 / 60, even more preferably 10 / 90 to 35 / 65, particularly preferably 15 / 85 to 35 / 65, and most preferably 20 / 80 to 30 / 70.
[0023] The molecular weight distribution of component (B) may or may not have another peak. As shown in Figure 1, the peak having a maximum (B1) and the peak having a maximum (B2) may be separated or may partially overlap. From the viewpoints of storage stability and moldability of the resin composition, it is preferable that component (B) does not contain an inorganic filler having a particle size of 5.0 μm or more, or if it contains one, the content thereof is 3 mass % or less, more preferably 1 mass % or less, and even more preferably 0.5 mass % or less, based on component (B).
[0024] In addition to the above-mentioned effects, the resin composition of the present embodiment tends to have low thermal expansion, high elastic modulus, heat resistance, and flame retardancy due to the inclusion of the (B) component. The (B) component may be used alone or in combination of two or more. If necessary, the (B) component may be used as a slurry in which it is dispersed in an organic solvent in advance. Examples of the (B) component include silica, alumina, mica, beryllia, aluminum carbonate, magnesium hydroxide, aluminum hydroxide, aluminum silicate, calcium carbonate, calcium silicate, magnesium silicate, silicon nitride, boron nitride, clay (calcined clay, etc.), molybdic acid compounds such as zinc molybdate, talc, aluminum borate, silicon carbide, etc. Among these, silica, alumina, mica, and talc are preferred, silica and alumina are more preferred, and silica is even more preferred, from the viewpoints of low thermal expansion, elastic modulus, heat resistance, and flame retardancy. Silica may be any of crushed silica, fumed silica, fused silica, and sol-gel silica. The shape of component (B) is not particularly limited, and may be amorphous, but from the viewpoint of significantly exhibiting the above-mentioned effect of the present embodiment, it is preferable that it is spherical. If it is spherical, the specific surface area becomes small, which is likely to lead to (1) a decrease in the "interface" between the inorganic filler and the resin component, and (2) a decrease in the amount of the surface treatment agent (coupling agent) on the surface of the inorganic filler, and as a result, the dielectric loss tangent (Df) is likely to be low.
[0025] The method for producing the component (B) used in this embodiment is not particularly limited, but examples include a method in which a crushed inorganic filler is put into a melting furnace and made into spheroids, which are then classified, and a method in which an inorganic filler is produced using a sol-gel method.
[0026] (B) Component Content In the resin composition of the present embodiment, the content of the (B) component is not particularly limited, but in any case, from the viewpoints of thermal expansion coefficient, elastic modulus, heat resistance, and flame retardancy, it is preferably 5 to 95 mass %, more preferably 10 to 80 mass %, even more preferably 10 to 65 mass %, even more preferably 15 to 60 mass %, particularly preferably 25 to 60 mass %, and most preferably 35 to 55 mass %, relative to the total amount of solids in the resin composition.
[0027] In addition, the (B) component may be used in combination with a coupling agent as necessary for the purpose of improving the dispersibility of the (B) component and the adhesion between the (B) component and the resin component in the resin composition. Examples of the coupling agent include a silane coupling agent and a titanate coupling agent. The coupling agent may be used alone or in combination of two or more types. As the coupling agent, a silane coupling agent is preferred. Examples of the silane coupling agent include epoxysilane coupling agents, aminosilane coupling agents, vinylsilane coupling agents, phenylsilane coupling agents, alkylsilane coupling agents, alkenylsilane coupling agents, alkynylsilane coupling agents, haloalkylsilane coupling agents, siloxane coupling agents, hydrosilane coupling agents, silazane coupling agents, alkoxysilane coupling agents, chlorosilane coupling agents, (meth)acrylic silane coupling agents, isocyanurate silane coupling agents, ureidosilane coupling agents, mercaptosilane coupling agents, sulfide silane coupling agents, isocyanate silane coupling agents, etc. Among these, the effect of the present embodiment tends to be easily manifested when aminosilane coupling agents and vinylsilane coupling agents are used. When using a coupling agent, the treatment method may be a so-called integral blend treatment method in which the inorganic filler is blended in the resin composition and then the coupling agent is added, but a method of using an inorganic filler that has been surface-treated in advance with a coupling agent in a dry or wet manner is preferred. By adopting the latter method, low thermal expansion, high elastic modulus, heat resistance and flame retardancy can be more effectively achieved. In other words, it is preferable that the (B) component has been surface-treated with a coupling agent.
[0028] (Other ingredients) The resin composition of the present embodiment may further contain other components, which are not particularly limited, but preferably contain at least one selected from the group consisting of (C) elastomer, (D) compatibilizer, (E) curing accelerator, flame retardant, flame retardant assistant, antioxidant, adhesion improver, heat stabilizer, antistatic agent, UV absorber, pigment, colorant, and lubricant.
[0029] ((C) Elastomer) The resin composition of the present embodiment is not particularly limited, but from the viewpoint of dielectric loss tangent (Df), it is preferable that it contains (C) elastomer [hereinafter, also referred to as (C) component]. In the present disclosure, an elastomer is defined as a polymeric compound that exhibits rubber elasticity at 25°C. The rubber elasticity is preferably an elastic modulus (Young's modulus) of 1 to 10 MPa. Examples of the component (C) include styrene-based elastomers, olefin-based elastomers, urethane-based elastomers, polyester-based elastomers, polyamide-based elastomers, acrylic-based elastomers, and silicone-based elastomers. The component (C) may be used alone or in combination of two or more types.
[0030] As the (C) component, from the viewpoint of dielectric loss tangent (Df), styrene-based elastomer is preferable, and styrene-based thermoplastic elastomer is more preferable. As the styrene-based elastomer, it is sufficient that it has a structural unit derived from a styrene-based compound, and from the viewpoint of dielectric loss tangent (Df), adhesion to a conductor, heat resistance, and low thermal expansion, one or more selected from the group consisting of hydrogenated styrene-butadiene-styrene block copolymer (SEBS or SBBS), hydrogenated styrene-isoprene-styrene block copolymer (SEPS), and styrene-maleic anhydride copolymer (SMA) are preferable, one or more selected from the group consisting of hydrogenated styrene-butadiene-styrene block copolymer (SEBS) and hydrogenated styrene-isoprene-styrene block copolymer (SEPS) are more preferable, and hydrogenated styrene-butadiene-styrene block copolymer (SEBS) is even more preferable. The styrene-based elastomer (excluding the SMA) may be modified with an acid anhydride such as maleic anhydride, and examples thereof include SEBS modified with an acid anhydride such as maleic anhydride, and SEPS modified with an acid anhydride such as maleic anhydride. The acid value of the acid-modified styrene-based elastomer (excluding the SMA) is not particularly limited, but is preferably 2 to 20 mg CH3ONa / g, more preferably 5 to 15 mg CH3ONa / g, and even more preferably 7 to 13 mg CH3ONa / g. The acid value can be measured by a titration method using sodium methoxide (CH3ONa).
[0031] In the component (C), the content of structural units derived from styrene [hereinafter, may be referred to as "styrene content"] is not particularly limited, but from the viewpoints of dielectric loss tangent (Df), adhesion to a conductor, heat resistance, and low thermal expansion, it is preferably 5 to 80 mass%, more preferably 10 to 75 mass%, even more preferably 15 to 60 mass%, particularly preferably 18 to 45 mass%, and most preferably 18 to 40 mass%, and may be 5 to 30 mass%, 10 to 30 mass%, 25 to 60 mass%, 25 to 45 mass%, or 30 to 40 mass%. The weight average molecular weight (Mw) of the (C) component is not particularly limited, but is preferably 12,000 to 1,000,000, more preferably 30,000 to 500,000, may be 50,000 to 200,000, may be 100,000 to 200,000, may be 120,000 to 180,000, may be 50,000 to 100,000, or may be 65,000 to 90,000. In the present disclosure, the weight average molecular weight (Mw) is a value measured in terms of polystyrene by gel permeation chromatography (GPC), and more specifically, a value measured by the method described in the examples.
[0032] (C) Elastomer Content When the resin composition of the present embodiment contains the (C) component, the content of the (C) component is not particularly limited, but is preferably 1 to 35 mass%, more preferably 3 to 30 mass%, further preferably 5 to 25 mass%, and particularly preferably 10 to 20 mass%, based on the total amount of solids in the resin composition. When the (C) component content is equal to or more than the lower limit, a better dielectric loss tangent (Df) tends to be obtained, and when the (C) component content is equal to or less than the upper limit, good heat resistance, moldability, processability, and flame retardancy tend to be obtained.
[0033] (D) Compatibilizer When the resin composition of the present embodiment contains the (C) component, it is preferable that the resin composition further contains a (D) compatibilizer (hereinafter, sometimes referred to as (D) component), although there is no particular limitation thereon. The (D) component is not particularly limited as long as it can function as a compatibilizer for the (A) component and the (C) component. The (D) component may be used alone or in combination of two or more types. Although there are no particular limitations, from the viewpoint of compatibilizing the components (A) and (C), the component (D) is preferably a modified conjugated diene polymer, and more preferably is obtained by modifying (d1) a conjugated diene polymer having a vinyl group in the side chain [hereinafter, sometimes referred to as the component (d1)] with (d2) a maleimide compound having two or more N-substituted maleimide groups [hereinafter, sometimes referred to as the component (d2)]. The components (d1) and (d2) will be described in detail below.
[0034] ((d1) Conjugated diene polymer having vinyl groups in the side chains) The component (d1) is not particularly limited as long as it is a conjugated diene polymer having a vinyl group in the side chain, but is preferably a conjugated diene polymer having a plurality of vinyl groups in the side chain. From the viewpoints of dielectric properties and heat resistance, the number of vinyl groups contained in one molecule of the component (d1) is preferably 3 or more, more preferably 5 or more, and even more preferably 10 or more. The component (d1) may be used alone or in combination of two or more kinds.
[0035] In the present disclosure, the term "conjugated diene polymer" refers to a polymer of a conjugated diene compound, such as 1,3-butadiene, isoprene, 1,3-pentadiene, 2,3-dimethyl-1,3-butadiene, 2-phenyl-1,3-butadiene, and 1,3-hexadiene. The conjugated diene polymer may be a polymer of one kind of conjugated diene compound, or may be a polymer of two or more kinds of conjugated diene compounds. The conjugated diene polymer may be a copolymer of one or more conjugated diene compounds and one or more monomers other than the conjugated diene compounds. In this case, the polymerization method is not particularly limited and may be any of random polymerization, block polymerization, and graft polymerization.
[0036] Specific examples of the (d1) component include polybutadiene having a 1,2-vinyl group, butadiene-styrene copolymer having a 1,2-vinyl group, polyisoprene having a 1,2-vinyl group, etc. Among these, from the viewpoint of dielectric properties and heat resistance, polybutadiene having a 1,2-vinyl group and butadiene-styrene copolymer having a 1,2-vinyl group are preferred, and polybutadiene having a 1,2-vinyl group is more preferred. As the polybutadiene having a 1,2-vinyl group, butadiene homopolymer having a 1,2-vinyl group is preferred. The butadiene-derived 1,2-vinyl group contained in the component (d1) is a vinyl group contained in a structural unit derived from butadiene represented by the following formula (d1-1).
[0037] [ka]
[0038] When the (d1) component is a polybutadiene having a 1,2-vinyl group, the content of the structural unit having a 1,2-vinyl group (structural unit represented by the above general formula (d1-1)) relative to all structural units derived from butadiene constituting the polybutadiene [hereinafter sometimes abbreviated as vinyl group content] is preferably 50 mol% or more, more preferably 60 mol% or more, even more preferably 70 mol% or more, particularly preferably 80 mol% or more, and most preferably 84 mol% or more, from the viewpoints of compatibility with other resins, dielectric properties, low thermal expansion and heat resistance. In addition, there is no particular upper limit to the vinyl group content, and it may be 100 mol% or less. From the same viewpoint, the polybutadiene having a 1,2-vinyl group is preferably a 1,2-polybutadiene homopolymer.
[0039] The number average molecular weight (Mn) of component (d1) is preferably 400 to 4,000, more preferably 500 to 3,500, from the viewpoints of compatibility with other resins, dielectric properties, low thermal expansion, and heat resistance, and may be 2,000 to 3,500, 600 to 2,000, or 700 to 1,500. In the present disclosure, the number average molecular weight (Mn) is a value measured in terms of polystyrene by gel permeation chromatography (GPC), and more specifically, a value measured by the method described in the examples.
[0040] ((d2) Maleimide compound having an N-substituted maleimide group) The component (d2) may be any maleimide compound having an N-substituted maleimide group, and may be a maleimide compound having one N-substituted maleimide group or may be a maleimide compound having two or more N-substituted maleimide groups. The component (d2) may be used alone or in combination of two or more types.
[0041] Among these, the component (d2) is preferably at least one selected from the group consisting of aromatic bismaleimide compounds having preferably two N-substituted maleimide groups bonded to an aromatic ring and aromatic polymaleimide compounds having preferably three or more N-substituted maleimide groups bonded to an aromatic ring, as described in the description of the maleimide compound in the component (A) above, from the viewpoints of solubility in an organic solvent and suppression of gelation during the reaction, as well as compatibility with other resins of the resulting modified conjugated diene polymer, dielectric properties, low thermal expansion and heat resistance, and is more preferably an aromatic bismaleimide compound having preferably two N-substituted maleimide groups bonded to an aromatic ring. In particular, from the same viewpoints as above, the component (d2) is more preferably a compound represented by the following general formula (d2-1):
[0042] [ka] (In the formula, R d1 and R d2 are each independently an aliphatic hydrocarbon group having 1 to 5 carbon atoms. d1 is an alkylene group having 1 to 5 carbon atoms, an alkylidene group having 2 to 5 carbon atoms, an ether group, a sulfide group, a sulfonyl group, a carbonyloxy group, a keto group, a single bond, or a divalent group represented by the following general formula (d2-1-1). q1 and q2 each independently represent an integer of 0 to 4.
[0043] R d1 and R d2 Examples of the aliphatic hydrocarbon group having 1 to 5 carbon atoms represented by include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a t-butyl group, an n-pentyl group, etc. As the aliphatic hydrocarbon group, from the viewpoints of compatibility with other resins and suppression of gelation during the reaction, an aliphatic hydrocarbon group having 1 to 3 carbon atoms is preferred, an alkyl group having 1 to 3 carbon atoms is more preferred, and an ethyl group or a methyl group is even more preferred.
[0044] X d1Examples of the alkylene group having 1 to 5 carbon atoms represented by include a methylene group, a 1,2-dimethylene group, a 1,3-trimethylene group, a 1,4-tetramethylene group, a 1,5-pentamethylene group, etc. As the alkylene group, an alkylene group having 1 to 3 carbon atoms is preferable, and a methylene group is more preferable. X d1 Examples of the alkylidene group having 2 to 5 carbon atoms represented by include an ethylidene group, a propylidene group, an isopropylidene group, a butylidene group, an isobutylidene group, a pentylidene group, and an isopentylidene group. q1 and q2 each independently represents an integer of 0 to 4. From the viewpoints of availability, compatibility with other resins, and suppression of gelation during the reaction, each is preferably an integer of 0 to 2, and may be 0. From the viewpoints of compatibility with other resins and suppression of gelation during the reaction, it is preferable that q1+q2 is an integer of 1 or more, and it is more preferable that q1 and q2 are each 1 or 2, and it is even more preferable that each is 2. When q1 or q2 is an integer of 2 or more, a plurality of R d1 R d2 They may be the same or different from each other. In addition, X d1 The divalent group represented by general formula (d2-1-1) is as follows.
[0045] [ka] (In the formula, R d3 and R d4 Each of X is independently an aliphatic hydrocarbon group having 1 to 5 carbon atoms or a halogen atom. d2 represents an alkylene group having 1 to 5 carbon atoms, an alkylidene group having 2 to 5 carbon atoms, an ether group, a sulfide group, a sulfonyl group, a carbonyloxy group, a keto group, or a single bond. q3 and q4 each independently represent an integer of 0 to 4. * represents a bonding site.
[0046] R d3 and R d4 The aliphatic hydrocarbon group having 1 to 5 carbon atoms represented by R d1This is explained in the same way as in the case of X d2 The alkylene group having 1 to 5 carbon atoms and the alkylidene group having 2 to 5 carbon atoms represented by X d1 Examples of the alkylene group having 1 to 5 carbon atoms and the alkylidene group having 2 to 5 carbon atoms represented by the formula (I) are the same as those represented by the formula (I). Each of q3 and q4 is independently an integer of 0 to 4. From the viewpoint of availability, each of them may be an integer of 0 to 2, or may be 0 or 1, or may be 0. When q3 or q4 is an integer of 2 or more, a plurality of R d3 R d4 They may be the same or different from each other.
[0047] Examples of the compound represented by the general formula (d2-1) include 4,4'-diphenylmethane bismaleimide, 2,2-bis[4-(4-maleimidophenoxy)phenyl]propane, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, etc. Among these, 4,4'-diphenylmethane bismaleimide is preferred from the viewpoints of solubility in organic solvents and suppression of gelation during the reaction, as well as compatibility with other resins, dielectric properties, low thermal expansion, and heat resistance of the resulting modified conjugated diene polymer. As the component (d2), in addition to the compound represented by the above general formula (d2-1), 4-methyl-1,3-phenylene bismaleimide and the like are also preferably used.
[0048] (Reaction conditions) The method for reacting the component (d1) with the component (d2) is not particularly limited, and for example, a modified conjugated diene polymer can be obtained by charging the component (d1), the component (d2), a reaction catalyst, and an organic solvent in predetermined amounts into a reaction vessel, and reacting them while, as necessary, heating, keeping warm, stirring, etc. The reaction conditions in this step can be appropriately adjusted depending on the types of raw materials used, etc., but from the viewpoints of workability and suppression of gelation during the reaction, the reaction temperature is preferably 70 to 120°C, and the reaction time is preferably 0.5 to 15 hours.
[0049] As the reaction catalyst, a curing accelerator (E) described later can be used. Among these, from the viewpoint of obtaining sufficient reactivity while suppressing gelation during the reaction, organic peroxides are preferred, and α,α'-bis(t-butylperoxy)diisopropylbenzene is more preferred. The reaction catalyst may be used alone or in combination of two or more kinds.
[0050] In carrying out the above reaction, the amounts of the (d1) and (d2) components to be blended are determined based on the mole number (M v ) for 、 (d2) The number of moles of N-substituted maleimide groups in the component (M m ) ratio (M m / M v ) is preferably an amount of 0.01 to 0.5, more preferably 0.02 to 0.4, and even more preferably 0.04 to 0.3.
[0051] By the above reaction, at least a part of the vinyl group in the side chain of the (d1) component reacts with the N-substituted maleimide group in the (d2) component to produce a modified conjugated diene polymer. The resulting modified conjugated diene polymer has a substituent (x) in the side chain formed by the reaction of the vinyl group in the (d1) component with the N-substituted maleimide group in the (d2) component. The modified conjugated diene polymer preferably has a substituent (x) and a vinyl group (y) in a side chain. The vinyl group (y) is preferably a 1,2-vinyl group possessed by a structural unit derived from butadiene. The extent to which the substituent (x) is present in the modified conjugated diene polymer can be determined by the extent to which the vinyl group of the (d1) component has been modified by the (d2) component (hereinafter referred to as the "vinyl group modification rate"). From the viewpoints of compatibility with other resins, dielectric properties, low thermal expansion and heat resistance, the vinyl group modification rate is preferably 1% or more, that is, 1 to 100%, more preferably 1 to 95%, even more preferably 5 to 85%, even more preferably 10 to 80%, particularly preferably 25 to 80%, and most preferably 35 to 75%. The vinyl group modification rate is a value determined by the method described in the Examples.
[0052] The number average molecular weight (Mn) of the modified conjugated diene polymer is not particularly limited, but from the viewpoints of compatibility with other resins, dielectric properties, low thermal expansion and heat resistance, it is preferably 700 to 6,000, more preferably 800 to 5,000, even more preferably 900 to 4,500, and particularly preferably 1,000 to 4,000.
[0053] (D) Compatibilizer Content When the resin composition of the present embodiment contains the (D) component, the content of the (D) component is not particularly limited, but from the viewpoints of compatibility with other resin components, dielectric dissipation factor (Df), low thermal expansion property, and heat resistance, the content of the (D) component is preferably 1 to 40 mass%, more preferably 3 to 30 mass%, even more preferably 5 to 25 mass%, and particularly preferably 7 to 20 mass%, relative to the total amount of solids in the resin composition.
[0054] ((E) Curing Accelerator) The resin composition of the present embodiment preferably further contains (E) a curing accelerator (hereinafter, sometimes referred to as component (E)). Examples of the (E) component include amine-based curing accelerators, imidazole-based curing accelerators, phosphorus-based curing accelerators, organometallic salts, acid catalysts, and organic peroxides. In this embodiment, imidazole-based curing accelerators are not classified as amine-based curing accelerators. The (E) component may be used alone or in combination of two or more. As the (E) component, imidazole-based curing accelerators and organic peroxides are preferred, and organic peroxides are more preferred.
[0055] The imidazole-based curing accelerator is not particularly limited, but examples thereof include imidazole, 2-methylimidazole, 2-ethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-undecylimidazole, 1-benzyl-2-methylimidazole, 2-heptadecylimidazole, 4,5-diphenylimidazole, 2-methylimidazoline, 2-phenylimidazoline, 2-undecylimidazoline, 2-heptadecylimidazoline, 2-isopropylimidazole, 2,4-dimethylimidazole, 2-phenyl-4-methylimidazole, 2-ethylimidazoline, 2-isopropylimidazoline, 2,4-dimethylimidazoline, and 2-phenyl-4-methylimidazoline. The organic peroxide is not particularly limited, but examples thereof include dicumyl peroxide, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexyne-3, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane, t-butylperoxyisopropyl monocarbonate, and α,α'-bis(t-butylperoxy)diisopropylbenzene.
[0056] ((E) Content of hardening accelerator) When the resin composition of the present embodiment contains the component (E), the content of the component (E) is not particularly limited, but in any case, it is preferably 0.01 to 3 mass%, more preferably 0.05 to 2.5 mass%, further preferably 0.1 to 2.0 mass%, particularly preferably 0.3 to 1.5 mass%, based on the total amount of solids in the resin composition. When the content of the curing accelerator (E) is within the above range, better heat resistance, storage stability, and moldability tend to be obtained.
[0057] (Content of Components Other Than the Components (A) to (E)) When the resin composition of the present embodiment contains components other than the components (A) to (E) (flame retardants, flame retardant assistants, antioxidants, adhesion improvers, heat stabilizers, antistatic agents, UV absorbers, pigments, colorants, lubricants, and other components), the content of each of these components is not particularly limited, and may be, for example, 0.01 mass % or more, and may be 30 mass % or less, 20 mass % or less, 10 mass % or less, 5 mass % or less, 1 mass % or less, or none at all, relative to the total amount of solids in the resin composition.
[0058] (Organic solvent) From the viewpoint of ease of application, the resin composition of the present embodiment may contain an organic solvent, that is, may be a resin varnish. The organic solvent is not particularly limited, but includes alcohol-based solvents such as ethanol, propanol, butanol, methyl cellosolve, butyl cellosolve, and propylene glycol monomethyl ether; ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ether-based solvents such as tetrahydrofuran; aromatic solvents such as toluene, xylene, and mesitylene; nitrogen-containing solvents such as dimethylformamide, dimethylacetamide, and N-methylpyrrolidone; sulfur-containing solvents such as dimethylsulfoxide; and ester-based solvents such as γ-butyrolactone. From the viewpoint of solubility, ketone-based solvents are preferred, and methyl ethyl ketone is more preferred. The organic solvent may be used alone or in combination of two or more kinds.
[0059] The solid content concentration of the resin varnish of the present embodiment is not particularly limited, but is preferably 30 to 90 mass%, more preferably 40 to 80 mass%, and further preferably 45 to 60 mass%. When the solid content concentration of the resin varnish is within the above range, the resin varnish is easy to handle, the impregnation into the substrate and the appearance of the produced prepreg are good, and the coatability when forming a resin film is also good.
[0060] The resin composition of the present embodiment can be produced by mixing the (A) component, the (B) component, and the other components that may be used as necessary, and an organic solvent by a known method. At this time, each component may be dissolved or dispersed in the organic solvent while stirring. The mixing order, temperature, time, and other conditions are not particularly limited and can be set as desired.
[0061] [Prepreg] The prepreg of the present embodiment is a prepreg containing the resin composition of the present embodiment or a semi-cured product of the resin composition. The prepreg of this embodiment contains, for example, the resin composition of this embodiment or a semi-cured product of the resin composition and a sheet-like fiber substrate. The prepreg is formed using the resin composition of this embodiment and a sheet-like fiber substrate. For example, the resin composition of this embodiment is impregnated or coated on a sheet-like fiber substrate, and then heated and dried to semi-cure (B-stage), thereby obtaining a prepreg. As a heat-drying method, for example, a method of heating and drying in a drying oven at 80 to 200°C for 1 to 30 minutes can be adopted. Here, in the present disclosure, B-stage refers to bringing the material into a B-stage state as defined in JIS K6900 (1994).
[0062] The sheet-like fiber substrate may be a known sheet-like fiber substrate used in various laminates for electrical insulating materials. The material of the sheet-like fiber substrate may be inorganic fiber such as glass, such as E glass, D glass, S glass, Q glass, etc.; organic fiber such as polyimide, polyester, tetrafluoroethylene, etc.; or a mixture thereof. From the viewpoint of dielectric loss tangent (Df), the material of the sheet-like fiber substrate is preferably inorganic fiber, more preferably glass. These sheet-like fiber substrates have the shape of, for example, a woven fabric, a nonwoven fabric, a roving, a chopped strand mat, a surfacing mat, etc. The sheet-like fiber substrate is preferably a woven fabric.
[0063] [Resin film] The resin film of the present embodiment is a resin film containing the resin composition of the present embodiment or a semi-cured product of the resin composition. The resin film of this embodiment can be produced, for example, by applying the resin composition of this embodiment to a support, drying it by heating, and semi-curing (B-staging) as necessary. Examples of the support include a plastic film, a metal foil, and a release paper. The drying temperature and drying time may be appropriately determined depending on the amount of organic solvent used and the boiling point of the organic solvent used, but for example, a resin film can be suitably formed by drying at 50 to 200°C for 1 to 10 minutes.
[0064] [Laminate] The laminate of the present embodiment is a laminate having a cured product of the resin composition of the present embodiment and a metal foil. It can also be said that the laminate of the present embodiment is a laminate having at least one selected from the group consisting of the cured product of the resin composition of the present embodiment and the cured product of the prepreg of the present embodiment and a metal foil. The laminate of the present embodiment can be produced, for example, by disposing a metal foil on one or both sides of a single prepreg of the present embodiment, or by disposing a metal foil on one or both sides of a laminate obtained by stacking two or more prepregs of the present embodiment, and then by hot pressing. In the laminate obtained by this production method, the prepreg of the present embodiment is C-staged. In this disclosure, C-stage refers to bringing the prepreg into the C-stage state defined by JIS K6900 (1994). Note that a laminate having a metal foil is sometimes called a metal-clad laminate. The metal of the metal foil is not particularly limited, but from the viewpoint of electrical conductivity, it may be copper, gold, silver, nickel, platinum, molybdenum, ruthenium, aluminum, tungsten, iron, titanium, chromium, or an alloy containing one or more of these metal elements, with copper and aluminum being preferred, and copper being more preferred. The conditions for hot and pressure molding are not particularly limited, but may be, for example, 100 to 300° C., 0.2 to 10 MPa, and 0.1 to 5 hours. In addition, the hot and pressure molding may employ a method in which a vacuum state is maintained for 0.5 to 5 hours using a vacuum press or the like.
[0065] [Printed wiring board] The printed wiring board of the present embodiment has a cured product of the resin composition of the present embodiment. It can also be said that the printed wiring board of the present embodiment has one or more selected from the group consisting of the cured product of the resin composition of the present embodiment, the cured product of the prepreg of the present embodiment, the resin film of the present embodiment, and the laminate of the present embodiment. The printed wiring board of this embodiment can be manufactured by performing a circuit formation process such as drilling, metal plating, and etching of metal foil by a known method using one or more selected from the group consisting of the prepreg of this embodiment, the resin film of this embodiment, and the laminate of this embodiment. Furthermore, a multilayer printed wiring board can be manufactured by performing a multilayer adhesion process as necessary. In the printed wiring board of this embodiment, the prepreg of this embodiment and the resin film of this embodiment are C-staged.
[0066] [Semiconductor package] The semiconductor package of the present embodiment is a semiconductor package having the printed wiring board of the present embodiment and a semiconductor element. The semiconductor package of the present embodiment can be manufactured by mounting a semiconductor element such as a semiconductor chip or memory at a predetermined position on the printed wiring board of the present embodiment and sealing the semiconductor element with a sealing resin or the like.
[0067] The resin composition, prepreg, resin film, laminate, printed wiring board, and semiconductor package of the present embodiment can be suitably used in electronic devices that handle high-frequency signals of 10 GHz or more. In particular, the printed wiring board is useful as a printed wiring board for millimeter-wave radar.
[0068] Although preferred embodiments have been described above, these are merely examples for the purpose of explaining the present disclosure, and the scope of the present disclosure is not limited to these embodiments. The present disclosure also includes various aspects different from the above-described embodiments, provided that they do not deviate from the gist of the disclosure. EXAMPLES
[0069] The present embodiment will be specifically described below with reference to examples, although the present embodiment is not limited to the following examples.
[0070] In each example, the number average molecular weight (Mn) and weight average molecular weight (Mw) were measured by the following methods. (1. Method for measuring number average molecular weight (Mn) and weight average molecular weight (Mw)) The values were calculated from a calibration curve using standard polystyrene by gel permeation chromatography (GPC). The calibration curve was approximated by a third-order equation using standard polystyrene: TSKstandard POLYSTYRENE (Type; A-2500, A-5000, F-1, F-2, F-4, F-10, F-20, F-40) [manufactured by Tosoh Corporation, product name]. The measurement conditions for GPC are shown below. Device: Pump: L-6200 type [manufactured by Hitachi High-Technologies Corporation] Detector: L-3300 type RI [Hitachi High-Technologies Corporation] Column oven: L-655A-52 [Hitachi High-Technologies Corporation] Column: Guard column: TSK Guardcolumn HHR-L + column: TSKgel G4000HHR + TSKgel G2000HHR (all manufactured by Tosoh Corporation, product names) Column size: 6.0 x 40 mm (guard column), 7.8 x 300 mm (column) Eluent: Tetrahydrofuran Sample concentration: 30mg / 5mL Injection volume: 20μL Flow rate: 1.00mL / min Measurement temperature: 40℃
[0071] Furthermore, the volume average particle size (D50) of the component (B) used in each example was measured by the following method. (2. Measurement method of D50 / particle size distribution) The cumulative particle size distribution was measured using a particle size distribution measuring device "Microtrac MT3000" (manufactured by Microtrac Bell Co., Ltd.). The operating procedure is as follows. First, an operation of circulating methyl isobutyl ketone in the apparatus and then discharging it was repeated three times, and then methyl isobutyl ketone was introduced again to replace the inside of the apparatus with methyl isobutyl ketone. A slurry of spherical silica (solid content concentration 60 to 70 mass%, dispersion solvent: methyl isobutyl ketone) was added to methyl isobutyl ketone so as to achieve a scattering intensity within a predetermined range, and the cumulative particle size distribution was then measured using the resulting dispersion with the above-mentioned device. The measurement parameters were refractive index input mode as transmission, sphere as aspheric, particle refractive index as 1.45, and dispersion medium refractive index as 1.40. The D50 value was obtained from the obtained cumulative particle size distribution.
[0072] (3. Measurement of the modification rate of vinyl groups) The value obtained by the following method was taken as the modification rate of the vinyl group of the modified conjugated diene polymer. The liquid containing the (d1) and (d2) components before the start of the reaction and the liquid containing the (D) modified conjugated diene polymer obtained after the reaction were subjected to GPC measurement in the same manner as described above. The reduction rate of the peak area derived from the (d2) component before and after the reaction, i.e., (peak area derived from the (d2) component before the reaction - peak area derived from the (d2) component after the reaction) x 100 / (peak area derived from the (d2) component before the reaction) was calculated, and the obtained value was regarded as the modification rate of the vinyl group.
[0073] Manufacturing Example 1 (Production of Modified Conjugated Diene Polymer D-1) The components (d1) and (d2), an organic peroxide, and toluene as an organic solvent in the amounts shown in Table 1 were placed in a 2 L glass flask equipped with a thermometer, a reflux condenser, and a stirrer, and reacted under stirring at 90 to 100°C for 5 hours in a nitrogen atmosphere to obtain a liquid containing a modified conjugated diene polymer D-1 (toluene diluted solution, solids concentration: 35% by mass). The vinyl group modification rate and number average molecular weight of the resulting modified conjugated diene polymer D-1 are shown in Table 1. [Table 1]
[0074] The details of each component listed in Table 1 are as follows. [Component (d1)] Polybutadiene 1:1,2-polybutadiene homopolymer, number average molecular weight = 1,200, vinyl group content = 85% or more [(d2) component] Bismaleimide compound 1: 4,4'-diphenylmethane bismaleimide [Reaction catalyst] Organic peroxide: α,α'-bis(t-butylperoxy)diisopropylbenzene
[0075] [Example 1, Comparative Examples 1 to 4] Each component shown in Table 2 was mixed with methyl ethyl ketone at room temperature under stirring according to the composition shown in Table 2 to prepare a resin varnish (resin composition) having a solid content concentration of 55 mass %. The resin varnish obtained above was applied to a glass cloth (NE glass, manufactured by Nitto Boseki Co., Ltd.) having a thickness of 0.08 mm, and then heated and dried at 105° C. for 4 minutes to produce a prepreg having a solid content of about 75% by mass derived from the resin varnish. Low-profile copper foil (SI-VSP18, manufactured by Mitsui Mining & Smelting Co., Ltd., the above-mentioned "VSP" is a registered trademark) having a thickness of 18 μm was placed on the top and bottom of this prepreg so that the M side (matte side) was in contact with the prepreg, and then heated and pressurized at a temperature of 190° C., a pressure of 3.0 MPa, and a time of 80 minutes to produce a double-sided copper-clad laminate (thickness: 0.60 mm). The resin composition or double-sided copper-clad laminate obtained in each example was evaluated according to the following methods. The results are shown in Table 2.
[0076] [Evaluation method] (4. Dielectric tangent (Df)) The outer copper foil of the double-sided copper-clad laminate obtained in each example was removed by immersing it in a copper etching solution (a 10% by mass solution of ammonium persulfate, manufactured by Mitsubishi Gas Chemical Co., Ltd.), and a test piece was cut into a length of 60 mm and a width of 2 mm, and the dielectric loss tangent (Df) was measured by the cavity resonator perturbation method. The measuring device used was a vector network analyzer "N5222B" manufactured by Agilent Technologies, the cavity resonator was "CP129" (10 GHz band resonator) manufactured by Kanto Electronics Application Development Co., Ltd., and the measurement program was "CPMA-V2". The measurement was performed under the conditions of a frequency of 10 GHz and a measurement temperature of 25°C.
[0077] (5. Peel strength (adhesion strength with conductor)) The peel strength was measured using "EZ-Test / CE" manufactured by Shimadzu Corporation according to the following method. The copper foil of each double-sided copper-clad laminate obtained in each example was processed into a 3 mm wide straight line by etching, and then dried at 105°C / hour to prepare a test piece. The test piece was used to measure the peel strength by peeling the copper foil in a 90° direction. The pulling speed was 50 mm / min.
[0078] (6. Circuit Embedding - Minimum Melt Viscosity) The prepregs prepared in each example were punched out to a diameter of 20 mm, and several sheets were stacked until the thickness was about 1 mm to prepare a measurement sample. Using a rheometer (manufactured by Rheometrics, product name: ARES-2K STD-FCO-STD), the viscosity of the measurement sample was measured under conditions of a temperature rise rate of 3°C / min, a load of 0.2 N, and a measurement temperature range of 50 to 200°C, and the minimum melt viscosity was determined. The lower the minimum melt viscosity, the better the circuit embeddability.
[0079] (7. Heat resistance (solder heat resistance)) The copper foil of the double-sided copper-clad laminate prepared in each example was etched to prepare a test piece. After a pressure cooker test (PCT) under the following conditions was carried out for 1 hour, the double-sided copper-clad laminate was immersed in molten solder at 288°C for 20 seconds. The heat resistance of the double-sided copper-clad laminate was then evaluated according to the following evaluation criteria. <Pressure cooker test conditions> 121℃, 0.22MPa, 100% relative humidity <Evaluation criteria for heat resistance> A: Upon visual inspection, no blisters were found. C: Upon visual inspection, blisters were found.
[0080] [Table 2]
[0081] Each component listed in Table 2 is explained below. [(A) Thermosetting resin] Maleimide compound A-1: Indan ring-containing aromatic bismaleimide Maleimide compound A-2: 4,4'-diphenylmethane bismaleimide
[0082] [(B) Inorganic filler] Spherical silica B-1: Spherical silica surface-treated with aminosilane coupling agent, D50=1.0μm Spherical silica B-2: Spherical silica surface-treated with aminosilane coupling agent, D50=2.0μm
[0083] [(C) Elastomer] Thermoplastic elastomer C-1: Styrene-ethylene-butylene-styrene copolymer (SEBS), styrene content 34% by mass, weight average molecular weight (Mw) = 147,000
[0084] [(D) Compatibilizer] Modified conjugated diene polymer D-1: Modified conjugated diene polymer D-1 obtained in Production Example 1
[0085] [(E) Curing accelerator] Curing accelerator E-1: α,α'-bis(t-butylperoxy)diisopropylbenzene, organic peroxide
[0086] [Flame retardant] Flame retardant 1: 1,2-bis(2,3,4,5,6-pentabromophenyl)ethane
[0087] From the results in Table 1, it is clear that the resin composition produced in Example 1 was able to reduce the dielectric tangent (Df) and improve the circuit embedding property. Furthermore, it is also found that the peel strength is improved and the heat resistance is excellent.
Claims
1. A thermosetting resin composition comprising (A) a thermosetting resin and (B) an inorganic filler, The (B) inorganic filler has a peak maximum (B1) and a peak maximum (B2) in a particle size distribution, the average particle size (b1) of the inorganic filler corresponding to the entire peak having the maximum (B1) is greater than the average particle size (b2) of the inorganic filler corresponding to the entire peak having the maximum (B2), and the content of the inorganic filler corresponding to the entire peak having the maximum (B1) relative to the content of the inorganic filler corresponding to the entire peak having the maximum (B2) is 1 / 99 to 40 / 60.
2. The resin composition according to claim 1, wherein the average particle size (b1) of the inorganic filler corresponding to the entire peak having the maximum (B1) is 1.5 μm or less.
3. The resin composition according to claim 1, wherein the average particle size (b2) of the inorganic filler corresponding to the entire peak having the maximum (B2) is greater than 1.5 μm.
4. 2. The resin composition according to claim 1, wherein the thermosetting resin (A) comprises at least one selected from the group consisting of an epoxy resin, a maleimide compound, a modified polyphenylene ether resin, a phenolic resin, a polyimide resin, a cyanate resin, an isocyanate resin, a benzoxazine resin, an oxetane resin, an amino resin, an unsaturated polyester resin, an allyl resin, a dicyclopentadiene resin, a silicone resin, a triazine resin, and a melamine resin.
5. The resin composition according to claim 1 , further comprising (C) an elastomer.
6. The resin composition according to claim 5 , further comprising (D) a compatibilizer.
7. The resin composition according to claim 1 , further comprising (E) a curing accelerator.
8. A prepreg comprising the resin composition according to claim 1 or a semi-cured product of the resin composition.
9. A resin film comprising the resin composition according to claim 1 or a semi-cured product of the resin composition.
10. A laminate comprising the cured resin composition according to claim 1 and a metal foil.
11. A printed wiring board comprising a cured product of the resin composition according to claim 1.
12. A semiconductor package comprising the printed wiring board according to claim 11 and a semiconductor element.
Citation Information
Patent Citations
Insulation resin material, resin film for interlayer insulation and production method of the same, composite film and production method of the same, and printed wiring board and production method of the same
JP2018012777A